Higher risk sexual behaviour is associated with unawareness of HIV-positivity and lack of viral suppression – implications for Treatment as Prevention. Issue 1 (December 2017) - Huerga, Helena; Venables, Emilie; Ben-Farhat, Jihane; van Cutsem, Gilles; Ellman, Tom; Kenyon, Chris
Abstract Efficacy of Treatment as Prevention Strategy depends on a variety of factors including individuals' likelihood to test and initiate treatment, viral load and sexual behaviour. We tested the hypothesis that people with higher risk sexual behaviour are less likely to know their HIV-positive status and be virologically suppressed. A cross-sectional population-based survey of individuals aged 15–59 years old was conducted in 2013 in KwaZulu-Natal, South Africa. A two-stage cluster probability sampling was used. After adjustment for age and sex, lack of awareness of HIV-positivity was strongly associated with having more than one sexual partner in the preceding year (aOR: 2.1, 95%CI: 1.5–3.1). Inconsistent condom use was more common in individuals with more than one sexual partner (aOR: 16.6, 95%CI: 7.6–36.7) and those unaware (aOR: 3.7, 95%CI: 2.6–5.4). Among people aware of their HIV-positivity, higher risk sexual behaviour was associated with lack of viral suppression (aOR: 2.2, 95%CI: 1.1–4.5). Risky sexual behaviour seems associated with factors linked to poor health-seeking behaviour which may have negative implications for HIV testing and Treatment as Prevention. Innovative strategies, driven by improved epidemiological and anthropological understanding, are needed to enable comprehensive approaches to HIV prevention.